Patient Experience of Herpes Zoster Disease in Argentina: Validation of a Health-Related Quality of Life Conceptual Model - Belizan, Maria (2024)
Objectives: Herpes zoster (HZ) substantially affects patients’ health-related quality of life (HRQoL), both in the acute phase and also in those developing postherpetic neuralgia (PHN). Building upon a previous qualitative concept elicitation study in Canada, we adopted a similar approach to further understand the patient experience of HZ/PHN in Argentina and impact on quality of life and qualitatively validate the previously published conceptual model for Argentina. Methods: (1) Comprehensive literature review of HZ impact on HRQoL in Latin America. (2) Qualitative concept elicitation interviews with participants aged $50 years with acute HZ or PHN. Verbatim interview transcripts underwent thematic and content analysis related to symptoms and impacts. Results: Studies from the literature (n = 6) identified 5 dimensions of HZ impact on HRQoL: pain management, disease management, family life, work, and emotional impact. A total of 10 participants were interviewed (5 acute HZ and 5 with PHN) with a mean age of 68.5 years (range 50-77 years) and 60% female. All participants reported rash and pain (some reporting a migratory element), fatigue (7 of 10), and itchiness (4 of 10). HRQoL domains most commonly affected were activities of daily living (9 of 10), emotional functioning (8 of 10), physical functioning (8 of 10), and sleep (7 of 10). Emergent themes on disease management included the need for greater public disease awareness/education, participants with PHN seeking alternative/traditional medical therapies. Conclusions: This study qualitatively validates the previously reported HRQoL conceptual framework. HZ symptoms, especially acute and chronic pain, substantially impair various aspects of HRQoL, prompting some participants to seek out alternative medical treatments.